Pendidikan Teologis-Saintifik Integralistik dalam Pusaran Era Globalisasi dan Revolusi Industri 4.0 (Prosiding Keislaman dan Sains, 2025)
The world has entered the era of globalization and the era of industrial revolution generation 4.0. Responding to the era of Globalization and Industrial Revolution 4.O, education is needed to face the challenges of globalization and Industrial Revolution 4.0. Based on this, the author is interested in discussing how Integralistic Theological-Scientific Education is in the Vortex of the Era of Globalization and Industrial Revolution 4.0. The aim of this research is to obtain Integralistic Theological-Scientific Education. The research method developed is qualitative with data collection techniques from various sources, including books and journals, scientific articles or literature reviews. The results of this research found: first, all theories work together to Islamize science and integrate it. Second, Integralistic Scientific-Theological Education in the Vortex of the Era of Globalization and Industrial Revolution 4.0 includes: the realm of faith, the moral realm, the realm of psychology, the realm of social knowledge, the realm of skills. Third, it was found that there were differences in the integration models developed. Even though there are differences, the direction is essentially the same.
Keywords: Educational; Theological; Scientific; Integralistik